Peran Guru Dalam Penggunaan Media Interaktif Pada Mata Pelajaran IPA Kelas V di SD Negeri 95 Palembang - Lia Wahyuni (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2024)
The teacher's role in determining the success of learning is very important. Learning activities will run more smoothly with media, especially interactive media. This research aims to explore the role of teachers in utilizing interactive media in science subjects. The method used is a descriptive qualitative method with the research subjects being class teachers and class V students. While the sample was taken through purposive sampling, data collection techniques involved observation, interviews and documentation. The research results show that teachers prepare material, give students opportunities to ask questions, use learning media, provide rewards to motivate students, and provide kahoot media as learning evaluation. The interactive media used is the Kahoot application. The use of interactive media in science learning at SD Negeri 95 Palembang has an important role in increasing students' interest and enthusiasm for learning. Keywords: Motivator; Mediator; Facilitator; Kahoot;